Determinan Belanja Modal Pemerintah Kabupaten/Kota Di Provinsi Bangka Belitung - Putri, Julia Maharani; Faridah, Faridah; Hartaty, Sri (Politeknik Negeri Ambon, 2024)
Knowing and analyzing how PAD, Balancing Funds, and SiLPA affect capital expenditure in Regencies/Cities in Bangka Belitung Province is the purpose of this study. Researchers used purposive sampling to select 6 out of 7 Regencies/Cities in Bangka Belitung in 2014-2023 to be studied. The data used are Budget Realization Reports in the Regency/City Government Reports in Bangka Belitung Province sourced from the official website djpk.kemekeu.go.id. The multiple regression analysis method used in this study is IBM SPSS 26. Balancing funds and SiLPA have a role in forming capital expenditure. Finally, PAD has an impact on capital expenditure.